세입자 보호를 위한 공적 장부의 주소정보 연계방안 연구 - 도로명주소대장을 중심으로 - 김정현; 강승모; 임미화; Kim, Jeong-Hyeon; Kang, Seung-Mo; Lim, Mi-Hwa (지적과 국토정보, 2023)
In recent times, there has been a surge in media coverage regarding fraudulent real estate lease scams. These scams have been attributed to speculators who made imprudent gap investments, in response to the sudden decline in real estate prices. The government has established new measures to safeguard tenants and prevent fraudulent real estate lease schemes in response to the growing incidence of tenants falling victim to such scams. Although there have been active research efforts on laws and regulations aimed at protecting tenants, such as the Tenant Protection Act and leasehold registration orders, there is an urgent need for research on the consistency of information across public ledgers, as real estate fraud has surged due to information asymmetry among these ledgers. This study aims to explore matching methodologies using matching keys for building information from real estate-related public ledgers, such as the building register and the road name address ledger, as well as to examine ways to integrate these ledgers with other public ledgers. 최근 급상승된 부동산 가격의 하락으로 무리하게 갭투자를 한 투기꾼들로 인한 부동산 전세 사기와 관련된 언론 보도가 급증하고 있다. 이로 인한 세입자의 피해 사례가 계속 증가함에 따라 정부는 세입자 보호와 전세사기 방지를 위한 대책을 수립하고 있다. 그동안 주택임대차보호법, 임차권등기명령 등 세입자 보호를 목적으로 하는 법령에 관한 연구는 활발히 진행되고 있으나, 공적 장부간 정보 불일치로 인한 사기가 급증하면서 공적 장부의 정보의 일관성에 관한 연구가 시급한 실정이다. 본 연구는 부동산과 연관성이 높은 건축물대장, 도로명주소대장의 건물정보를 매칭키를 활용한 매칭방법론에 대한 연구를 모색하고 다른 공적 장부와의 연계방안도 검토하고자 한다.